Atributos de solo do bioma cerrado sob diferentes usos e manejo - OLIVEIRA, Carloeme Alves de (2009)
This work aimed to assess physical and chemical attributes (texture, porosity, mean particle density, dry bulk density, flocculation degree, aggregation, hydraulic conductivity and penetration resistance, pH-CaCl2, calcium, magnesium, potassium, phosphorus and base saturation) along the transections of two cerrado (savannah) soils. Additionally, efficiency of the forestry remnants on the retention of sediments originated from agricultural activities was observed. The following soils were studied: 1. One site Typic Haplustox Latossolo Vermelho Distrófico (Panamá, Goiás, Brazil), cropped under conventional tillage system; 2. Two sites Typic Haplustept Cambissolo Háplico Eutrófico (Goiatuba and Jandaia, Goiás, Brazil), cropped under no-tillage system and Brachiaria pasture. Riparian forests at downstream of all cropped areas were found. Morphologic description of soil profiles and penetration resistance tests were performed. Deformed and undeformed soil samples at depths of 0-5, 5-10 and 10-20 cm for chemical and physical analyses were collected. For comparison of means Tukey-test at 5% probability was used. Management systems caused the following changes on physical and chemical attributes in comparison to riparian forests: a) Lower penetration resistance under no-tillage system on the Typic Haplustox soil, and a higher one on the Typic Haplustept soils; b) decrease of soil aggregation both under conventional and no-tillage systems, and increase under pasture; c) decrease of soil organic matter and calcium under all cropping systems. Soil morphological descriptions on the riparian forests showed layers of non pedogeneticized materials over the A horizons, likely originated from the upstream areas, from where terraces have been withdrawn. Riparian forests downstream the cropped areas under no-tillage and pasture systems, due to the unsuitable width and anthropic actions, were not able to retain satisfactorily the ran off sediments; under conventional tillage, however, this width was considered to be suitable in conformity to Brazilian environmental laws